Travels of Aly Bey (Domingo Badia y Leblich) in Morocco, Tripoli, Cyprus, Egypt, Arabia, Syria and Turkey. - Badia y Leblich, Domingo, 1767-1818. (Frankfurt am Main)
1. c. (xlii, 339, [5] s., xliv y. resim, plan (kimi katlı), [2] katlı sayfa harita)